Ten little rabbits - Sendak, Maurice (Harper, an imprint of HarperCollinsPublishers, 2024)
This enchanting picture book introduces the beloved author to a new generation of readers, encouraging them to count from one to ten and back again as they watch the magic unfold before their very eyes.